A desigualdade de gênero: uma análise do caso brasileiro - Carvalho, Luiza Vosgrau de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of this article is to analyze the evolution of gender inequality in Brazil using PNAD (National Household Sample Survey) data comparing the period of 2002 and 2015 with the decomposition of the Gini index, and verifying if there were an increase or decrease of this inequality in relation to the population income, also using as a form of analysis the percentiles of the wages of the female and male salaried population in the mentioned years. Other related analyzes are the relationships between gender and race inequalities, the evolution of women in the labor market, the comparison of years of studies between men and women, and the position of Brazil in the comparative ranking of global gender inequality

O objetivo deste artigo é analisar a evolução da desigualdade de gênero no Brasil utilizando como base os dados da PNAD (Pesquisa Nacional por Amostra de Domicílios) comparando, por meio da decomposição do índice de Gini, o período de 2002 e 2015 e verificar se houve um aumento ou diminuição dessa desigualdade em relação à renda populacional, utilizando também como forma de análise os percentis dos salários da população assalariada feminina e masculina nos anos mencionados. Outras analises adjacentes são as relações entre as desigualdades de gênero e raça, a evolução das mulheres no mercado de trabalho, a comparação de anos de estudos entre homens e mulheres e em que posição se encontra o Brasil no ranking comparativo da desigualdade de gênero mundial
Keywords: Discriminação de sexo contra as mulheres; Igualdade; Igualdade - Brasil; Discriminação racial; Equality